Gaming addiction and exercise addiction within the framework of behavioral addictions - Denizci Nazlıgül, Merve; Yılmaz, Adviye Esin (Journal of Dependence, 2019)
The meaning of the term ‘addiction’ has been changed with both social and technological developments during recent years. In the past, addiction was referred to taking psychoactive chemicals; however, this construct involves not only substance-related but also behavioral addictions nowadays. Gaming addiction, exercise addiction or shopping can be accepted as examples of behavioral addictions, although gambling disorder has only been recognized as an official psychiatric disorder. Indeed, relatively little is known about most of the behavioral addictions since those addictions which are part of daily life have hedonistic in nature. The aim of the current study is to examine closely both gaming addiction and exercise addiction and discuss their differences and similarities in the context of behavioral addictions.
Keywords: Addictive behavior; video games; problems and exercises; gaming addiction